The Integrated Software “Algebra, 7 Classes” (Journal of Information Technologies in Education (ITE), 2007)
The software “Algebra, 7 classes” was created for computer support of lessons of algebra in 7 class of general school. In this article the items of information on its purpose and basic descriptions are resulted.